2019
DOI: 10.1038/s41598-019-44686-2
|View full text |Cite|
|
Sign up to set email alerts
|

Quality of life after photo-selective vaporization and holmium-laser enucleation of the prostate: 5-year outcomes

Abstract: This study was aimed to compare serial long-term postoperative changes in quality-of-life (QoL) between photoselective-vaporization (PVP) using 120W-High-Performance-System and holmium-laser-enucleation (HoLEP) in benign-prostatic-hyperplasia (BPH) patients and to identify factors influencing the QoL improvement at the short-term, mid-term and long-term follow-up visits after surgery. We analyzed 1,193 patients with a baseline QoL-index ≥2 who underwent PVP (n = 439) or HoLEP (n = 754). Surgical outcomes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
0
10
0
1
Order By: Relevance
“…It can be postulated that HoLEP in AT patients is equally effective as in no AT patients. Moreover, it is of note that several studies [ 26 , 27 ] reported on ongoing improvements within the first 6 months after HoLEP and thus, these very early results at discharge will invariably be subject to further improvements.…”
Section: Discussionmentioning
confidence: 99%
“…It can be postulated that HoLEP in AT patients is equally effective as in no AT patients. Moreover, it is of note that several studies [ 26 , 27 ] reported on ongoing improvements within the first 6 months after HoLEP and thus, these very early results at discharge will invariably be subject to further improvements.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding objective parameters, Elmansy et al and Sun et al reported a significant improvement in Qmax after HoLEP in a comparison between PVP and HoLEP. 11,12 The present data showed that, although there was no difference in the improvement in Qmax between the two groups, the improvement in PVR in the TUEB group was superior to that in the PVP group. This supports the fact that enucleation is better than PVP for improving objective parameters.…”
Section: Discussionmentioning
confidence: 41%
“…A comparison between PVP and HoLEP reported that stress urinary incontinence was more frequently observed in the HoLEP group. 12 Stress urinary incontinence is considered to be a characteristic complication of enucleation. Stress urinary incontinence is usually caused by the weakness and stretching of the external sphincter due to an enlarged prostate.…”
mentioning
confidence: 99%
“…The follow-up time ranged from 12 months to 60 months. Among the enrolled studies, 12 studies [ 10 13 , 15 18 , 20 , 22 , 23 , 25 ] (4392 patients) compared L-EEP and L-EVP.…”
Section: Resultsmentioning
confidence: 99%